Analysis of the cool islands in the Zaragoza's parks in winter: Article - Ferrández Pastor, Óscar (Geographicalia, 2023)
Cities have a different climate than their surroundings since they generate heat by themselves, and this is what is known as an ‘urban heat island’. The parks mitigate these effects because they generate freshness and soften the temperatures, making these places very pleasant in the hot months. This cooling effect of the parks is called ‘cool island’ and depends mainly on the size of the city and the park itself, although they influence more variables. In the case of Zaragoza, a 3.3 oC drop in temperature has been measured at night, with favourable conditions, in the Grande J. A. Labordeta park.
Keywords: urban heat island; cool island; park; temperature; Zaragoza